Lab-made 100 bp DNA Ladder using Polymerase Chain Reaction and Human DNA - Bariqi, Muhammad Ilmam; Yamamoto, Zulham; Firjatu, Putri Chalya; Nasution, Luthfi Umam Hakim; Lubis, Oryza Sativa (Makara Journal of Science, 2026)
Polymerase chain reaction (PCR) is a rapid, molecular biology technique widely used in disease diagnosis and genetic engineering. Conventional PCR products require agarose gel electrophoresis, which employs a DNA ladder as a size reference. Most commercial ladders are plasmid-based and reliable but require additional culture time. We suggest a more efficient method for producing a DNA ladder using DNA derived from human blood. DNA was isolated using a commercial kit. Primer sets generating 100–1000 base pair (bp)-long fragments bearing target regions p12, p13, and p14 were designed using Primer-BLAST. DNA was amplified by routine PCR, visualized on a 1% (w/v) agarose gel, and pooled to form a 100-bp ladder. The lab-made ladder was compared with a commercial ladder. Extracted DNA showed a purity of 1.878. Bands of 100, 500, and 1000 bp were added in greater amounts to produce wider, more visible bands. The pooled fragments served as a functional 100-bp DNA ladder. A key limitation is the lack of sequencing, as genomic variations may affect flanking regions and potentially alter amplicon sizes. A 100-bp DNA ladder generated using DNA extracted from human blood had good quality, comparable to that of a commercial ladder.